KORUPSI DI DAERAH : SALAH JALAN PENYELENGGARAAN ADMINISTRASI DAERAH - Bhairawa Putera, Prakoso (Pusjar SKPP Lembaga Administrasi Negara, 2012)
Implementation of regional autonomy in Indonesia provides an important record, which the granting authority to local governments to develop policies and manage budgets, creates the domination of power by local elites. It brings the local elites close to and have access to the sources of corruption-prone areas or abuse of authority. This is what gave rise to the new form of decentralized corruption (corruption in regional administration). According on the KPK during 2004 - 2011 there were 42.06% of the total number of cases of corruption made in the level or by local officials. Primary and recurrent mode of corruption in the region is the markup of the procurement of goods and services, fictitious expenses and projects for their own advantage. Misguided practice of the administration area (corruption in the region) could be reduced by involving as broad as possible the public participation in the presence of anti-corruption movement which next would transformed into a social movement and simultaneous in all regions of Indonesia. Keywords : Corruption, regional administration, civil society, anti- corruption movement. Pelaksanaan otonomi daerah di Indonesia memberikan catatan penting, dimana pemberian kewenangan kepada pemerintah daerah untuk menyusun kebijakan dan pengelolaan anggaran, menciptakan dominasi kekuasaan oleh elit lokal. Dominasi tersebut membawa elit lokal sangat dekat dan memiliki akses terhadap sumber-sumber daerah yang rawan korupsi atau penyalahgunaan wewenang. Hal inilah yang kemudian memunculkan wacana baru berupa desentralisasi korupsi (korupsi di daerah). Berdasarkan data KPK selama 2004 – 2011 terdapat 42,06% dari total jumlah kasus tindak pidana korupsi dilakukan di tingkat atau oleh pejabat daerah. Modus utama dan berulang dari korupsi di daerah adalah markup dari pengadaan barang dan jasa, pengeluaran fiktif dan proyek-proyek untuk keuntungan diri sendiri. Praktik salah jalan penyelenggaraan administrasi daerah (korupsi di daerah) dapat ditekan dengan melibatkan seluas mungkin partisipasi masyarakat dengan adanya gerakan anti-korupsi yang menjelma menjadi gerakan sosial dan serentak di seluruh wilayah Indonesia. Kata kunci: Korupsi, administrasi daerah, civil society, gerakan anti- korupsi